The Economic Decolonisation of Indonesia: A Bird's-eye View - J Thomas Lindblad (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2011)
This contribution offers an abridged account of the process of economic decolonisation as it unfolded between 1945 and 1959, from the proclamation of independence until the nationalisation of the vast majority of Dutch-owned companies that had retained operations in Indonesia after independence.1 Four themes serve as devices tofurther our understanding of the process of economic decolonisation. These four themes, in order of appearance, are below: the new spirit in Indonesian economic life following the transfer of sovereignty; the changing climate of economic policy-making during the 1950s; the response and accommodation by remaining Dutch companies; and, finally, the concluding phase of expropriation and nationalisation.